Biochar soil amendments affect mycorrhizal colonization, root nodulation and dry matter accumulation in cowpeas (Vigna unguiculata (L.) Walp.) - UZOH, Ifeyinwa Monica; RAMADILE, Keabetswe Chriscellda; CHUKWUDI, Uchechukwu Paschal; IGIEHON, Ozede Nicholas; AKANMU, Akinlolu Olalekan; BABALOLA, Olubukola Oluranti (Studia Universitatis Babeș-Bolyai Biologia, 2025)
There is increasing demand for renewable inputs to improve soil productivity to satisfy the ever-growing human population. Biochar as a renewable resource has attracted attention over the years as soil amendment, notable for climate change mitigation and crop improvement. This study assessed the impact of pine wood biochar soil amendments on mycorrhizal root colonization, root nodulation, growth and yield of cowpeas in 2017 and 2018. The experimental design was a randomized complete block design with three replications. Biochar was applied with or without inorganic fertilizer (NPK15:15:15), cattle dung and nutrient source control two weeks before planting cowpea. Data on growth parameters, number of nodules, and plant dry matter accumulation were collected. Mycorrhizal colonization and spore counts associated with root nodules were determined under laboratory conditions. The results revealed that biochar amendments significantly affected nodulation, vine length, root length and weight. Percentage improvement was as follows: vine length by 8.8%, number of nodules by 14%, root length by 9.5%, root weight by 5.2% and dry matter accumulation by 92%. Application of NPK improved root length and weight over the control. Stereomicroscopic visualization of the roots indicated high presence of arbuscules in the biochar treatment over the control. Biochar addition is essential for improvement of rhizosphere traits essential for plant growth enhancement. Article history: Received 24 September 2024; Revised 14 December 2024; Accepted 15 January 2025; Available online 25 June 2025